Synthesis and Characterization of Antifungal Nanocomposite AgSiO2 Polymethyl Methacrylate - Sabouhi, Mahmoud; Amini-Pozveh, Maryam; Bajoghli, Farshad; Dastjerd, Hamid reza; Mohammadi, Rasoul (European Journal of Dentistry, 2021)
Objectives Polymethyl methacrylate as the most common material used in denture bases has some problems. The aim of this study was to introduce a new nanocomposite of PMMA to improve flexural strength and antifungal properties.Materials and Methods In this experimental study, AgSiO2 nanoparticles were prepared, and their characteristics were confirmed by scanning electron microscope and energy dispersive spectroscopy techniques. Then the nanoparticles in the weight ratio of 0.1, 0.3, 0.5, and 0.7% were incorporated to heat-cured PMMA and the control group included no nanoparticles.To measure the flexural strength before and after thermocycling three-point bending test was used. Eight samples per group with dimensions of 65 × 10 × 2.5 mm were used. Antifungal activity against Candida albicans (PTCC 5027) was investigated through colony count method. Statistical analysis was done by SPSS at significance level of p-value ≤0.05.Results The mean flexural strength in groups 0.1, 0.3, and 0.7% was significantly higher than the control. After thermocycling flexural strength of the control group was significantly lower than 0.3 and 0.5% groups. As the concentration of nanoparticles increased the antifungal activity improved (p < 0.05).Conclusion Addition of nanoparticles AgSiO2 improved flexural strength and antifungal characteristics of PMMA.
Keywords: antifungal; Candida albicans; colony count; nanocomposite; polymethyl methacrylate; strength